Evaluation the Role of Securities Market in Increasing the Regional Budget Revenues - Miller, Aleksandr Yemelyanovich; Miller, Andrey Aleksandrovich (Economy of Regions, 2015)
In the article, the relevant problem of increasing the regional budget revenues is investigated. The subject matter of the research is the securities market as a mechanism for the redistribution of financial resources. The purpose of the research is justification of the effective scheme feasible in the current environment of the interaction of the securities market and the regional budget. In the study of the above-mentioned subject, the hypothesis of a close relationship between state and non-state finance system was taken as a basis. The theoretical principle of the research supports the theory of the stock market; to achieve the purpose, the institutionally-functional approach to the study of state finances is applied. As the result of the research, possible common grounds of the securities market and the regional financial system are identified; the reserve of improving efficiency of the securities market in the Western Siberia regions are revealed; the model reflecting the dependence of tax revenues from the pace of regional economic development is constructed; promising areas for development of the securities market for the benefit of the regional economy and regional financial system are formulated; the possible effect from the development of regional securities market on regional budget revenues is estimated. The results mentioned above are recommended to be apllied when developing regional financial policies and programmes of region socio-economic development. A long-term stimulation of the growth in incomes of regional budgets is a very complex process, but with the proper elaboration of organizational issues, the implementation of the proposed scheme for interaction of the securities market and the regional financial system is capable to provide a steady increase in tax revenue in the short term and alleviate the problem of financing costs of the regional budget.